PERTUMBUHAN SEMAI NYATOH (Palaquium sp.) PADA BERBAGAI PERBANDINGAN MEDIA DAN KONSENTRASI PUPUK ORGANIK CAIR DI PERSEMAIAN - Uminawar, Uminawar; Umar, Husain; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2013)
The aims of this research was to determine the effects of some growing medium and concentration of organic liquid fertilizer on the growth of Palaquium sp seedlings. The research was conducted from April to July 2013, at the Permanent Nursery, Tadulako University, Palu Central Sulawesi. The experiment was laid out in a Randomized Complete Design (RCD) with factorial pattern. First, growing medium consist of four treatments; soils/control (P0), Soils+Sand+Compos 1:1:1 (P1), Soils+Sand+Compos 2:1:1 (P2), Soils+Sand+Compos 3:1:1 (P3). Second, concentration of organic liquid fertilizer; 0 ppm/kontrol (C0), 1,0 ppm (C1), 1,5 ppm (C2) and 2,0 ppm (C3). Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant. The results of the study showed that there were significant differences between the treatments in all the parameters assessed. The highest seedling height increment (16,4 cm) was achieved by combination treatment between P2C2. The highest stem diameter increment (0,32 mm) was also achieved by combination treatment between P0C1. Hence, for the single effect of the treatments, the highest leaf number increment was achieved by Soils+Sand+Compos 2:1:1 treatment (P2) and concentration of organic liquid fertilizer 1,5 ppm (C2) with value 6,05 and 6,15 pieces, respectively. Keywords : Growing medium, Concentration of liquid fertilizer, Seedling growth Palaquium sp.